When Local Meets Global: How Introducing English Destabilizes Translanguaging Practices in a Cross-Border Organization - Langinier, Hélène; Ehrhart, Sabine (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2020)
Drawing on an interdisciplinary approach combining linguistics and International Business, we suggest that global and local dynamics interact to co-construct specific language practices in an MNC subsidiary situated in a cross-border territory. We show how introducing a foreign language can modify the benefits that these local multilingual practices generate.Employees revert to translanguaging: They combine all their language knowledge, French, German and local vernacular, to make themselves understood. These specific local language practices have an inclusive role that enables low-level employees in the hierarchy to play a linking role between the multinational company subsidiary and its headquarters in Germany.